Spirituality and Health Research Methods, Measurements, Statistics, and Resources. - Koenig, Harold G. (West Conshohocken : Templeton Press, 2012)
In Spirituality and Health Research: Methods, Measurement, Statistics, and Resources, Dr. Harold G. Koenig leads a comprehensive overview of this complex subject. Dr. Koenig is one of the world’s leading authorities on the relationship between spirituality and health, and a leading researcher on the topic. As such, he is distinctively qualified to author such a book.This unique source of information on how to conduct research on religion, spirituality, and health includes practical information that goes well beyond what is typically taught in most undergraduate, graduate, or even post-do.
14. Statistics I: General Considerations15. Statistics II: Statistical Tests and Approaches; 16. Confounders, Explanatory Variables, and Moderators; 17. Models and Mechanisms; 18. Statistical Modeling; Part 5: Publishing and Funding Resources; 19. Publishing Results; 20. Funding for Research; 21. Writing a Grant; Final Thoughts; Notes; Glossary; Index
Description based upon print version of record.
Keywords: Health Services Research; Medicine - Research - Methodology; Qualitative research; Religion and Medicine; Research Design; Spirituality; Medicine; Qualitative research; Medicine -- Research -- Methodology; Spirituality; MEDICAL / Research; Electronic books